Penentuan Kelayakan Karyawan Baru Menggunakan Data Mining Dengan Algoritma Decision Tree (C4.5) - Hamzah Kadar; Agus Budiyantara (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Eligibility for new employees includes individuals who have skills appropriate to the position they are applying for, have a high willingness to learn, communicate well, and have integrity and good work ethics. They must also be able to adapt to the work environment and team quickly, but determining the suitability of new employees is quite difficult given the competencies of each division, therefore the use of data mining is very suitable for determining the suitability of new employees according to the needs of the company which uses them. decision tree algorithm (C4.5), the results obtained from the decision tree algorithm process show the truth tree for classifying new employees and a high level of accuracy with a percentage of 98.44% based on test 2.